Extra-prostatic Transgene-associated Neoplastic Lesions in Transgenic Adenocarcinoma of the Mouse Prostate (TRAMP) Mice. (February 2015) - Berman-Booty, Lisa D.; Thomas-Ahner, Jennifer M.; Bolon, Brad; Oglesbee, Michael J.; Clinton, Steven K.; Kulp, Samuel K.; Chen, Ching-Shih; La Perle, Krista M. D.
Male transgenic adenocarcinoma of the mouse prostate (TRAMP) mice are frequently used in prostate cancer research because their prostates consistently develop a series of preneoplastic and neoplastic lesions. Disease progression in TRAMP mouse prostates culminates in metastatic, poorly differentiated carcinomas with neuroendocrine features. The androgen dependence of the rat probasin promoter largely limits transgene expression to the prostatic epithelium. However, extra-prostatic transgene-positive lesions have been described in TRAMP mice, including renal tubuloacinar carcinomas, neuroendocrine carcinomas of the urethra, and phyllodes-like tumors of the seminal vesicle. Here, we describe the histologic and immunohistochemical features of 2 novel extra-prostatic lesions in TRAMP mice: primary anaplastic tumors of uncertain cell origin in the midbrain and poorly differentiated adenocarcinomas of the submandibular salivary gland. These newly characterized tumors apparently result from transgene expression in extra-prostatic locations rather than representing metastatic prostate neoplasms because lesions were identified in both male and female mice and in male TRAMP mice without histologically apparent prostate tumors. In this article, we also calculate the incidences of the urethral carcinomas and renal tubuloacinar carcinomas, further elucidate the biological behavior of the urethral carcinomas, and demonstrate the critical importance of complete necropsies even when evaluating presumably well characterized phenotypes in genetically engineered mice.